2011
DOI: 10.5897/ajb11.463
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological responses to water and nutrient stress in oil palm

Abstract: The research was conducted to detect changes in growth, physiology and nutrient concentration in response to two watering regimes (well-watered and water-stress conditions) and to two nutrient regimes (with or without fertilization) of oil palm. Under stress conditions, changes in plant growth, dry matter allocation, relative water content, leaf relative conductivity, leaf N, P and K concentration are usually observed. These characteristics and related parameters were determined and the experiment results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 58 publications
1
12
0
4
Order By: Relevance
“…According to Reddy et al (2004) water stress negatively influenced various physiological processes of plant which caused considerable reductions in final productivity. It was observed that, leaf chlorophyll content was reduced under water stress condition of plants (Sun et al, 2011).This reduction in chlorophyll contents under water deficit conditions is mainly due to the production of ROS that deteriorate the chloroplasts (Gill & Tuteja, 2010).…”
Section: Effect Of Irrigation Intervals On the Growth Yield Contribumentioning
confidence: 98%
“…According to Reddy et al (2004) water stress negatively influenced various physiological processes of plant which caused considerable reductions in final productivity. It was observed that, leaf chlorophyll content was reduced under water stress condition of plants (Sun et al, 2011).This reduction in chlorophyll contents under water deficit conditions is mainly due to the production of ROS that deteriorate the chloroplasts (Gill & Tuteja, 2010).…”
Section: Effect Of Irrigation Intervals On the Growth Yield Contribumentioning
confidence: 98%
“…Efek dari rendahnya curah hujan terhadap produktivitas terlihat dalam kurun waktu 2-24 bulan kemudian. Hal tersebut terjadi karena tanaman mengalami kondisi cekaman kekeringan yang mempengaruhi kondisi fisiologis dan produktivitasnya (Henson, 2007;Zhang et al, 2007;Gardner et al, 2008;Palupi dan Dedywiyanto, 2008;Sun et al, 2011;Lakitan, 2012;Bakoume et al, 2013;dan Cha-um et al, 2013;Syarovy et al, 2015). Disisi lain, curah hujan yang sangat tinggi juga dapat menyebabkan penurunan rendemen minyak pada bulan yang sama akibat kelembaban yang berlebihan.…”
Section: Pendahuluanunclassified
“…Pemadatan tanah menyebabkan kerusakan sifat fisik tanah secara bertahap yang menganggu pertumbuhan dan fungsi akar (Yahya et al, 2010). Pertumbuhan dan fungsi akar yang terganggu menyebabkan gangguan dalam penyerapan hara dan air (Yahya et al, 2010;Sun et al, 2011;Jourdan et al,. 2000).…”
Section: Pendahuluanunclassified